DIPLOMASI INDONESIA TERHADAP NEGARA KONTRIBUTOR DALAM MISI UNIFIL (UNITED NATIONS INTERIM FORCE IN LEBANON) TAHUN 2016-2018 - Umma, Kharomatul; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research describes the Indonesia‟s diplomacy in a UNIFIL. The United Nations Interim Force in Lebanon (UNIFIL) was established by United Nations Security Council Resolutions 425 (1978) and 426 (1978) of 19 March 1978 and mandated to:  Confirm the withdrawal of Israeli forces from southern Lebanon, Restore international peace and security and Assist the Government of Lebanon in ensuring the return of its effective authority in the area.  This research will focus on how Indonesia‟s diplomacy in contributing Country in UNIFIL mission. This study interesting because describe about the diplomatic efforts of Indonesia  as developing country and the world‟s biggest peacekeeper troops in UNIFIL get a significant role.  This research was prepared using the perpective of Neorealis, the theory of Defence Diplomacy and the concept of national interest. This research used descriptive qualitative  research methods which the reseacrh data was obtained throught literature review.Indonesia’s Diplomacy in UNIFIL mission has resulted establish confidence  building measures by conducting joint military exercises, establish democratic civil and military relations  and increase the capability of the tool and troops especially martime task force Keywords: Diplomacy, Indonesia, UNIFIL, Peacekeeper, Maritime Task Force